FSGS: Diagnosis and Diagnostic Work-Up. (24th May 2016) - Sprangers, Ben; Meijers, Björn; Appel, Gerald
Abstract : Focal segmental glomerulosclerosis is a histologic lesion, rather than a clinical disease. FSGS is common cause of nephrotic syndrome in both adults and children worldwide. In the United States it is the most common primary glomerular disease resulting in end-stage renal disease and recent reports have suggested that its incidence might be on the rise. Currently the incidence is estimated to be 7 per million. The podocyte is the cellular target cell in FSGS and in recent years substantial insight in the pathogenesis and genetics of FSGS have accumulated. Furthermore the discovery of potential novel biomarkers to diagnose FSGS and monitor disease activity has renewed interest in this disease. In this review article we will focus on the clinical presentation and diagnosis of FSGS.